The Book of Lost Names - Harmel, Kristin (New York : Gallery Books, 2020)
Eva Traube Abrams, a semi-retired librarian in Florida, is shelving books one morning when her eyes lock on a photograph in a magazine lying open nearby. She freezes; it's an image of a book she hasn't seen in sixty-five years--a book she recognizes as The Book of Lost Names.
Includes bibliographical references.
Keywords: Women librarians -- Fiction; Photographs -- Fiction; World War, 1939-1945 -- Fiction -- Underground movements -- France; World War, 1939-1945 -- Fiction -- France; Jews -- Fiction -- France; Code and cipher stories; France -- Fiction -- History -- German occupation, 1940-1945; Historical fiction; Cryptologic fiction; War fiction